Chemical synthesis and applications of graphene and carbon materials - Antonietti, M.; Müllen, K. (Wiley-VCH, 2017)
This ready reference and handbook is unique in focusing on synthesis and the application of graphene and other carbon materials with an emphasis on chemistry aspects. It deals with top-down and bottom-up approaches, and presents the best synthetic methods.
Keywords: Graphene.; Carbon.; Charcoal.; elektronické knihy; electronic books